What Factors Affect Expenditures of Goods Services For Infrastructure In Indonesia - Sudaryo, Slamet; Rachmad R, Muhammad; Zamzami Zamzami; Muhammad Safri (Green Publisher, 2023)
This study identifies and analyzes the factors that influence infrastructure spending and their impact on regional economic growth in Indonesia. This study is based on cross-sectional data covering 32 provinces in Indonesia with time series 2008-2020 using multiple regression analysis models and simple regression panel data. The results of the study show that the Provincial Minimum Wage, Construction Support Workforce Growth, Regional Own Revenue and Total Provincial Government Expenditure are factors that have a significant influence on the allocation of goods/services expenditure for infrastructure. Meanwhile, the Construction Sector Workforce Growth factor and Gross Regional Domestic Product do not affect the allocation of goods/ services expenditure for infrastructure. The results of the study show that the allocation of goods/services spending for infrastructure has a significant negative effect on economic growth. When infrastructure spending increases by 1 million rupiah, economic growth will decrease by 8.58e-07 or 0.000000858%. While the implications of the results of this study should be that the central and regional governments prioritize spending on goods/services for infrastructure with programs related to reducing poverty and unemployment. Productive infrastructure development and maintaining the quality of work results.